Implementation of RME-based student worksheets on plane figure area material for students of phase b elementary school - Sulistiana Puji Lestari; Ika Rahmawati (Universitas Kanjuruhan Malang, 2023)
The purpose of this research is to find out the activities of students in determining the area of ​​​​flat shapes through drawing and constructing knowledge on student worksheets and to find out the effectiveness of the RME based student worksheets used. Qualitative descriptive method with design research was chosen in this study. This method is carried out by collecting data to obtain factual information that will be used to explain the process and information obtained in depth. The results showed that the RME approach based on local wisdom could be used to understand students material about the area of ​​plane figure and the RME-based student worksheets was considered effective for use in learning. So that educators can apply the RME approach with student worksheets to teach students about the area of ​​plane figures.